The effect of sustainability reporting on the financial performance and firm value among publicly listed firms in the Philippines in 2019 and 2020 - Alix, Martin Jiro S. (Animo Repository, 2023)
Sustainability reporting has seen a significant upward trend and has been gradually recognized as an integral contributor to the growth of businesses in recent times. Despite, however, its notable increase in prominence, sustainability reporting is still in its initial stages in the Philippines having only been made mandatory in 2019. Considering the situation, the study aimed to investigate the relationship between sustainability reporting and financial performance as measured by return on assets and return on equity as well the relationship between sustainability reporting and firm value as measured by Tobin's Q. The study was conducted on publicly listed firms in the Philippine Stock Exchange in 2019 and 2020 selected using a purposive sampling design. The study employed multivariate regression to test the hypotheses developed from legitimacy, stakeholder, and institutional theories and the sustainability reporting literature. The findings of the study indicated that on average, sustainability reporting disclosures had a significant association with financial performance and firm value except in 2019 and 2020 and that among the sustainability reporting variables, economic and social disclosures exhibited a significant but negative relationship with firm value while only social disclosures exhibited a significant but negative relationship with return on equity for 2019 and 2020. Such significant but negative associations, however, cannot be afforded with much relevance because of the low explanatory value between the tests and the variables. Through t-test, it was also found that financial performance and firm value were not significantly affected by the COVID-19 pandemic and that only environmental disclosures showed significant change from 2019 and 2020.